MORAL VALUES IN LADY GAGA’S SELECTED SONGS LYRIC - Yuni E. Alouw; Elizabeth Z. Oroh; Sanerita T. Olii (SoCul: International Journal of Research in Social Cultural Issues, 2021)
The purpose of this study is to reveal the moral values found in Lady Gaga’s selected songs. This research is a qualitative research since the data gathered are in the form of words rather than numbers. In analyze the data; the writer used objective approach because the data were taken only from the work itself, the study only focused on moral values found only in Lady Gaga’s selected song lyrics. The result show that There are four songs that full contain moral values. Born This Way morally tells about originality that needs to be sustained by human. Til It Hapens To You is a song to express the pain of women who become the victims of violation and sexual assault, Grigio Girls is composed to describe the mental strenth of female friends who got cancer and how they keep sustaining their life and Angel Down is about abuse of teenager, comes from the experience when a teenager was shot by neighbour, implying there is no care and protection to teens in their period of growth to future maturity, Til It Hapens To You is mainly about social moral that women needs to appreciated and respected, Grigio Girls delivers individual moral that tells that each individual needs to be strong and brave to face even hardest phase in life in this case cancer as acute disease, and Angel Down conveys social moral value with its concern to teenangers that needs to be given special attention in family and society. Keywords : Dynamic, Sisterhood Relationship, Moral Values, Literature.